Mixed convection and thermal radiation effects on non-Newtonian nanofluid flow with peristalsis and Ohmic heating - Alrashdi, Abdulwahed Muaybid A. (Frontiers in Materials, 2023)
Introduction: This investigation explores the heat and mass transfer properties of a non-Newtonian nanofluid containing graphene nano-powder and ethylene glycol during peristalsis. The rheological characteristics of the nanofluid are determined using the Carreau-Yasuda model, and various factors such as viscous dissipation, Lorentz force, Ohmic heating, and Hall effects are taken into account. Mixed convection and thermal radiation effects are also considered in the analysis, and the problem is mathematically described using the long wavelength and low Reynolds number approximations. Methods: The resulting nonlinear system is solved using numerical methods to obtain the solutions. The dominant effects of mixed convection and thermal radiation are given particular attention, while the influences of other parameters are discussed in relation to these dominant effects. Results and Discussion: The results demonstrate that increasing the Brinkman number, heat source, and thermal slip parameter leads to higher nanofluid temperatures. However, the heat transfer rate decreases with a higher Hall parameter. The velocity near the center of the channel increases for higher values of the concentration Grashof and Hall parameters. Furthermore, an increase in the Hall and Brownian motion parameters results in a higher concentration of nanoparticles. These findings have practical implications in various fields, including materials science, chemical engineering, and biomedical engineering.